Analisis Kesalahan Siswa Kelas X MIA dalam Menyelesaiakan Soal Sistem Persaaan Linear Tiga Variabel - Ina, Maria Apriani Cica; Lubur, Dorothea Novia Lodu (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research was motivated by the many difficulties experienced by students during the mathematics learning process which had an impact on errors in doing math problems. This research is qualitative descriptive research that aims to analyze, describe the types of errors made by students in solving mathematical problems on the material of three-variable linear equation systems. The subjects of this study were 3 students of class X MIA odd semester of the 2023/2024 academic year at SMAK St. Dominic Tambolaka. Data collection techniques in the form of written tests. Based on the results of data analysis, conclusions were obtained that showed that students made mistakes at the completion stage